Determinants of business and personal services: Evidence from West-German regions - Dietmar Dathe; Günther Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
In the Employment Guidelines for the year 2000, the European Commission stressed the need to develop a policy framework in order to fully exploit the employment potential of the service sector. This concern is especially related to Germany for its massive service gap compared to Anglo-Saxon (United States, United Kingdom) and Scandinavian countries (Denmark, Sweden) in general, and in personal and business services in particular. The focus of this study is to understand the theoretical basis of the dynamic of employment growth in services and to identify especially the determinants that foster the growth of business services and the creation of jobs in personal services in Germany. The paper starts therefore with an extensive literature review on service employment with a particular focus on business and personal services and on the German debate. – – In den beschäftigungspolitischen Leitlinien der Europäischen Kommission für 2000 wird die Notwendigkeit zur Schaffung politischer Rahmenbedingungen für die volle Ausschöpfung des Beschäftigungspotentials des Dienstleistungssektors hervorgehoben. Gerade für Deutschland, wo im Vergleich zu den Vereinigten Staaten und Großbritannien, aber auch im Vergleich zu skandinavischen Staaten wie Dänemark und Schweden, eine erhebliche Dienstleistungslücke herrscht, ist diese Einschätzung der Europäischen Kommission von großer Relevanz. Die Dienstleistungslücke betrifft insbesondere die Bereiche der unternehmens- und personennahen Dienstleistungen. Im Zentrum der Studie stehen die theoretischen Grundlagen der Beschäftigungsdynamik im Dienstleistungssektor und die Identifizierung jener Faktoren, die speziell das Wachstum unternehmensnaher Dienstleistungen und die Arbeitsplatzschaffung im Bereich personennaher Dienstleistungen fördern. Die Studie beginnt deshalb mit einem ausführlichen Literaturüberblick zur Dienstleistungsbeschäftigung mit Schwerpunkt auf die deutsche Debatte.
Keywords: 330